Tarjih Maqasidiy for the Placement of Terrorist Convicts in East Java - Dwi Aprilianto; Farida Ulvi Na'imah (Justicia Islamica, 2021)
Prisons have contributed significantly to the deradicalization process and served as a machine for positive changes for terrorist convicts. On the other hand, instead of isolating and making terrorist convicts repent, public prison is ideal for spreading radicalism understanding. Public prisons cannot prevent terrorist convicts from disseminating their extreme views. This research answered the pros and cons of placing terrorist convicts in public prisons or special prisons containing kindness, maslahah, and targets. This empirical research was processed descriptively. Data was collected through field research in Class I Prison in Surabaya and Class II Prison B in Lamongan through a phenomenological approach, interpretive paradigm, and analysis of Tarjih maqasidiy. This study concluded that the placement of terrorist convicts alongside non-terrorist convicts in public prisons caused more substantial damage (mafsadah arjah) than gathering terrorist convicts in one particular prison by taking the lighter one out of two mafsadah, mafsadah of radical doctrine, recruitment networks, and mafsadah of giving a chance for consolidation to terrorist convicts. This research answered the problem of placing terrorism convicts and formulated an efficient, effective, and targeted policy basis for terrorism convicts.